The Emergence and Molecular Characteristics of New Delhi Metallo β-Lactamase-Producing Escherichia coli From Ducks in Guangdong, China - Wang, Min-Ge; Yu, Yang; Wang, Dong; Yang, Run-Shi; Jia, Ling; Cai, Da-Tong; Zheng, Si-Lin; Fang, Liang-Xing; Sun, Jian; Liu, Ya-Hong; Liao, Xiao-Ping (Frontiers in Microbiology, 2021)
The aim of this study was to determine the prevalence and transmission characteristics of NDM-producing Escherichia coli from ducks in Guangdong, China. In this study, a total of 28 NDM-producing E. coli isolates were recovered from 88 unduplicated diseased duck samples (31.8%) from veterinary clinics in Guangzhou, Foshan, Qiangyuan and Huizhou. Two variants blaNDM-1 and blaNDM-5 were detected and the latter was present in 89.6% of the isolates (25/28). MLST analysis indicated that these E. coli isolates possessed 6 distinct STs and ST156 was the most prevalent followed by ST648, ST746, ST354, ST10 and ST162. In addition, Phylogenomic analysis found that two of the isolates that were recovered from a single sample possessed different genomes, and the blaNDM-carrying IncX3 plasmids maybe horizontal transfer between E. coli isolates in the intestinal tracts of ducks. WGS analysis further revealed that blaNDM co-existed with other 25 types ARGs, of which, 16 ARGs were highly prevalent with detection rates >50%, and the high incidence of co-producing blaNDM and mcr-1 E. coli isolates (22/88, 25.0%) was detected in ducks. This study underscores the importance of surveillance for blaNDM-harboring microbes in ducks and suggests that the possibility of carbapenem resistance spread from poultry production chains to humans.